2020
DOI: 10.12662/2317-3076jhbs.v8i1.3410.p1-7.2020
|View full text |Cite
|
Sign up to set email alerts
|

Influência das condições de bem-estar domiciliar na prática do isolamento social durante a Pandemia da Covid-19

Abstract: Objetivo: avaliar a influência de elementos de bem-estar domiciliar na prática do isolamento social durante a pandemia da COVID-19. Métodos: estudo realizado mediante pesquisa de opinião conduzida por meio de redes sociais e aplicativos de internet. Utilizou-se o modelo de regressão logística multinomial para estimar a probabilidade de influência das variáveis analisadas no nível de isolamento social. Resultados: as variáveis relacionadas ao bem-estar domiciliar contribuem para aumentar a probabilidade de o in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
7
0
5
Order By: Relevance
“…Sleep deprivation is a recurring factor in epidemic events that require social isolation. Therefore, maintaining habits (such as healthy eating habits, physical activities, and sleep hygiene) is essential to minimize negative effects on health during this time 21 ; 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Sleep deprivation is a recurring factor in epidemic events that require social isolation. Therefore, maintaining habits (such as healthy eating habits, physical activities, and sleep hygiene) is essential to minimize negative effects on health during this time 21 ; 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Frente à impossibilidade de controle imediato da pandemia por redução de susceptíveis por meio de vacinação, as experiências mundiais apontam para a necessidade de controle da velocidade de progressão da curva por meio de medidas de isolamento físico social [R40]. Esta medida tende reduzir a necessidade de suporte ventilatório e a internação em unidades de terapia intensiva em curto espaço de tempo, adequando a necessidade à capacidade assistencial do sistema de saúde (DA SILVA et al, 2020;GARCIA et al, 2020;ZIMMERMANN et al, 2020) [R45]. Em contrapartida, políticas públicas sociais precisam ser repensadas no Brasil, sobretudo aquelas voltadas a proteção dos trabalhadores, investimentos no sistema de saúde e a garantia de proteção profissional (RAFAEL et al, 2020) A adoção de medidas mais rígidas provavelmente teria prevenido casos, internações, óbitos e pressão sobre os sistemas de saúde (OPAS, 2020d).…”
Section: Discussionunclassified
“…In a recent survey (Bezerra et al, 2020), it was observed that the average number of people per household during social isolation in the interviewed group was 3.2 people and that the highest percentage of respondents are experiencing isolation in homes with 2 to 4 people. Other data demonstrated that elements related to the quality of homes, such as green and open areas, space for sports practice, among others, influence the probability of adopting social isolation (Silva et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The numbers may reach even worse rates because during contamination by SARS-COV-2 at least 19 million adults had multimorbidity, which is the presence of at least two comorbidities, and it increases the risk of death (Nunes et al, 2017). In Brazil, 46% of the elderly respondents in Brazil indicate that they are terrified of being infected (DATAFOLHA, 2020), and this is reinforced by the high probability of them being in isolation (Silva et al, 2020). It is also why the group of people aged 60 or over was substantially withdrawn from work due to pandemics.…”
Section: Discussionmentioning
confidence: 99%